PENGARUH WORK FAMILY CONFLICT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DIMEDIASI OLEH KOMITMEN ORGANISASI - Ratya Shafira Arifiani; Viajeng Purnama Putri (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study discusses conflicts that help workers in dealing with work or family, namely work family conflicts. Work family conflicts are conflicts faced because they cannot balance or harmonize work and family. The impact of work family conflicts varies, from employee performance, OCB to organizational commitment. The object of this research is workers who are married and have fixed working hours. This study aims to see what conflicts have an impact on organizational commitment and OCB. This study uses a quantitative approach with explanatory research. Data were collected based on questionnaires distributed to respondents and analyzed using path analysis with the SmartPLS 3 program. The results showed: 1) work family conflict has no effect on OCB; 2) Work family conflict affects organizational commitment; 3) organizational commitment has an effect on OCB; and 4) organizational commitment to mediate the effect of family conflict work on OCB.